Caracterização e estudo do efeito do extrato hidroalcoólico do epicarpo liofilizado do Syzygium cumini L. em ratos espontaneamente hipertensos (SHR) - Nascimento, Suênia Maria do (2015)
Hypertension and diabetes are diseases with a strong impact on public health and have risk factors, incorrect eating habits and oxidative stress. In this sense, the science search for alternatives to the treatment of these diseases, being natural compounds an important research line. Family Myrtaceae species are recognized as a major source of antioxidant compounds and stands out Syzygium cumini L. to present biological activities, especially hypoglycemic. Currently, one observes during the processing of this and other plants a wide production waste (eg .: fruit epicarp and seeds) without proper biological utilization and / or therapeutic. This study aims to identify the content of phenolic compounds, antioxidant activity of the hydroalcoholic extract lyophilized epicarp of S. cumini L. (Sc-EPHE), and investigate the effects of chronic intake of this extract in normotensive rats metabolism (WKY) and hypertensive (SHR). To characterize the Sc-Ephesus was carried out by high-performance liquid chromatography, the identification of gallic acid as a marker of standardization, determination of total phenolic and antioxidant activity. During six weeks the animals received via different oral doses (150 or 300 mg/kg) of Sc-EpHE or saline (VEHICLE) in this period the weight was measured weekly and water intake and ration monitored daily. After treatment the animals underwent direct measurement of blood pressure, blood collection and later euthanized for collection agencies. The modified extraction technique generated a product with high content of phenolic compounds (5440.86 mg GAE/100g sample), presence of gallic acid and high antioxidant activity (EC50 = 59 μg/ mL) determined by DPPH. As for biological assessments, there was no significant difference between groups for weight gain. The average blood pressure levels (MAP) in SHR VEHICLE (153.8±5.0 mmHg) were significantly higher than WKY VEHICLE (123.0±4.86 mmHg). Treatment with 150 mg/kg Sc-EpHE did not significantly alter the MAP. However hypertensive rat 300 mg/ kg of Sc- EpHE reduced 29.77 ± 8.12 mmHg of MAP compared to vehicle. The contractile response induced to phenylephrine was significantly higher in SHR VEHICLE (Emax = 153.4± 14.2%) compared to WKY VEHICLE (Emax = 100.2±10.5%). SHR treated with 300 mg/kg Sc- EpHE (Emax = 116.7 ± 6.7%) showed reduced contractile response to phenylephrine in SHR compared to vehicle. The induced vasorelaxation NPS in SHR 150 mg/kg was not changed, however the SHR 300 mg/kg (Emax = 82.2 ± 3.7%) the effect was reduced as compared with WKY VEHICLE (Emax = 100.0 ± 4.7%). The SHR 300 mg/kg showed a significant reduction in fasting blood glucose during the fourth (25.5 ± 7.06 mg/dL) and fifth (30.83±7.06 mg/dL) week of treatment. Fluorescence microscopy preliminary results suggest that the SHR have excessive production of reactive oxygen species (ROS) and treatment with 300 mg/kg Sc-EpHE attenuate this production. Therefore, our results demonstrate that the Sc- EpHE has a high content of phenolics and antioxidant activity, and suggest that oral administration Sc-EpHE has antihypertensive activity for attenuating the contractile response, and possibly, the production of ROS and reduce glucose levels in SHR.